Polyethylene glycol versus lactulose in the treatment of chronic functional constipation in children: A randomized clinical trial - Hassan Talakesh; Alizamen Salehifard Jouneghani; Karamali Kasiri; Farnoush Kochekian; Afsaneh Malekpour Tehrani (Journal of Shahrekord University of Medical Sciences)
Background and aims: Constipation in children is a serious problem that affects both children and their families. We aimed to compare the clinical efficacy of lactulose and polyethylene glycol in the treatment of constipation in children. Methods: This randomized clinical trial was performed on 92 patients referred to a private gastroenterology clinic in Shahrekord, Iran. The patients were randomly assigned into two groups receiving polyethylene glycol or lactulose. Defecation patterns and complications were assessed 0, 3, 7, and 21 days after the intervention. Data were analyzed using the chi-square test, repeated measures test, Mann–Whitney U test in SPSS version 16.0. P<0.05 was considered statistically significant. Results: No difference was found between the two interventional groups in terms of the frequency of painful defecation (P=0.31), fecal incontinence (P=0.50), hard stools (P=0.69), fear of defecation (P=0.09), poor appetite (P=0.29), straining at stool (P=0.50), and abdominal pain (P=0.07) within a follow-up period of 21 days. There were significant differences in the frequency of defecation on days 7 and 21 (P=0.02). The mean frequencies of abdominal cramps were significantly higher in those who received lactulose (P=0.001). The rate of nausea and vomiting was 10.6% in the lactulose group and 4.3% in the polyethylene glycol group, indicating no difference between the two groups (P=0.221). Conclusion: The administration of polyethylene glycol and lactulose had no significant difference in reducing the symptoms of chronic functional constipation in children. However, it seems that polyphenol glycol played a role in increasing the frequency of defecation.